Auditory Perceptual Abilities Are Associated with Specific Auditory Experience - Zaltz, Yael; Globerson, Eitan; Amir, Noam (Frontiers in Psychology, 2017)
The extent to which auditory experience can shape general auditory perceptual abilities is still under constant debate. Some studies show that specific auditory expertise may have a general effect on auditory perceptual abilities, while others show a more limited influence, exhibited only in a relatively narrow range associated with the area of expertise. The current study addresses this issue by examining experience-dependent enhancement in perceptual abilities in the auditory domain. Three experiments were performed. In the first experiment, twelve pop and rock musicians and 15 non-musicians were tested in frequency discrimination (DLF), intensity discrimination (DLI), spectrum discrimination (DLS), and time discrimination (DLT). Results showed significant superiority of the musician group only for the DLF and DLT tasks, illuminating enhanced perceptual skills in the key features of pop music, in which miniscule changes in amplitude and spectrum are not critical to performance. The next two experiments attempted to differentiate between generalization and specificity in the influence of auditory experience, by comparing subgroups of specialists. First, seven guitar players and eight percussionists were tested in the DLF and DLT tasks that were found superior for musicians. Results showed superior abilities for DLF for guitar players, demonstrating a dependency of auditory learning on the specific area of expertise. Subsequently, a third experiment was conducted, testing a possible influence of vowel density in native languages on auditory perceptual abilities. Ten native speakers of German (a language characterized by a dense vowel system of 14 vowels), and ten native speakers of Hebrew (characterized by a sparse vowel system of five vowels), were tested in a formant discrimination task. This is the linguistic equivalent of a DLS task. Results showed that German speakers had superior formant discrimination, demonstrating highly specific effects for auditory linguistic experience as well. Overall, results suggest that auditory superiority is associated with the specific auditory exposure.